2018
DOI: 10.1186/s12885-018-4786-7
|View full text |Cite
|
Sign up to set email alerts
|

A review of sex-related differences in colorectal cancer incidence, screening uptake, routes to diagnosis, cancer stage and survival in the UK

Abstract: BackgroundColorectal cancer (CRC) is an illness strongly influenced by sex and gender, with mortality rates in males significantly higher than females. There is still a dearth of understanding on where sex differences exist along the pathway from presentation to survival. The aim of this review is to identify where actions are needed to improve outcomes for both sexes, and to narrow the gap for CRC.MethodsA cross-sectional review of national data was undertaken to identify sex differences in incidence, screeni… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

35
189
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 285 publications
(228 citation statements)
references
References 78 publications
35
189
3
1
Order By: Relevance
“…This study provided no evidence of an association between SES and the rate of increase in incidence of either proximal or distal tumours, in contrast to previous studies where higher incidence rates were observed in more deprived groups. Although factors associated with an increased risk of colorectal cancer, such as obesity, low‐fibre diet and reduced physical activity, are known to be associated with lower SES, changes in obesity prevalence trends are actually similar between socioeconomic groups; this may partly explain the lack of association between SES and colorectal cancer incidence rate increases in the present study. Furthermore, obesity is one of many risk factors associated with the development of colorectal cancer, and is itself caused by several complex societal, genetic and environmental interactions.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation
“…This study provided no evidence of an association between SES and the rate of increase in incidence of either proximal or distal tumours, in contrast to previous studies where higher incidence rates were observed in more deprived groups. Although factors associated with an increased risk of colorectal cancer, such as obesity, low‐fibre diet and reduced physical activity, are known to be associated with lower SES, changes in obesity prevalence trends are actually similar between socioeconomic groups; this may partly explain the lack of association between SES and colorectal cancer incidence rate increases in the present study. Furthermore, obesity is one of many risk factors associated with the development of colorectal cancer, and is itself caused by several complex societal, genetic and environmental interactions.…”
Section: Discussionmentioning
confidence: 54%
“…Although men are well recognized to have a higher incidence of colonic and rectal cancer in older age groups, there is little difference in the incidence rates between men and women aged less than 40 years. UK data have shown that men have a higher proportion of rectal tumours, but that women have a higher proportion of right‐sided tumours. However, data on anatomical subsite have not been linked to age‐specific incidence trends in the UK population.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, differences in fat distribution might contribute to the persistent inflammation associated with GERD and the development of Barrett's oesophagus [82]. Other examples of sex differences in the biology of GI cancers are as follows: in colorectal cancer, a breakdown by anatomical site shows that the proportion of cases in the rectum and sigmoid are higher in men (31.5% and 23.1%, respectively), as compared to 23.1% and 20.4% [83]. In contrast, the proportion of cases in the caecum and ascending colon are higher in women (17.2 versus 9.8%) [83].…”
Section: Sex Differences In the Pharmacology Of Anticancer Drugsmentioning
confidence: 99%
“…Colorectal cancer is one of the most commonly occurring cancers in men and women worldwide as well as one of the most common causes of death from cancer [1]. Due to exogenous and/or endogenous factors, the mortality of colorectal cancer is higher in men than women [2]. Colorectal cancer mainly affects older adults, but the incidence is rising among the young population [3].…”
Section: Introductionmentioning
confidence: 99%